Formation of Models of «Green» Entrepreneurship Based on Market Segmentation, Taking into Account the Principles of Responsible Consumption - O. V. Kozhevinа; L. A. Belyaevskaya-Plotnik (Модернизация, инновация, развитие, 2022)
The article is a continuation of a number of scientific studies carried out by the authors within the framework of government assignments and grants devoted to identifying the relationship between the economic security of territories and the development of “green” entrepreneurship models on them.Purpose: is to identify the relationship between responsible consumption and ensuring the economic security of subjects of the "green" economy in the context of the global principles of sustainable development and the transformation of consumer preferences.Methods: the study is based on the methodology and principles of sustainable development in "green" entrepreneurship. The use of comparative and comparative analysis methods is due to the need to identify the features of sustainable (responsible) production and consumption in different sectors of the "green" economy. Comparative marketing allows you to clarify the category of "sustainable (responsible) consumption", systematize international experience and best practices of "green" marketing.Results: the authors have identified the most promising market segments of the "green" economy, outlined the advantages of companies that implement the principles of "green" marketing and take into account ESG factors in business models of entrepreneurship. The use of indicative analysis tools made it possible to determine the level of development of individual segments of "green" entrepreneurship in the constituent entities of the Russian Federation. Based on the results of Russian practice and on the example of the implementation of the national project "Labor Productivity", the effectiveness of the implementation by companies participating in the national project of responsible and lean production is substantiated. The structural components of the "green" economy and economic security are revealed, the differentiation of Russian regions is shown in the context of indicators of the development of individual segments of the "green" economy. It has been determined that all segments of the "green" economy in Russia are covered by the national project "Labor Productivity".Conclusions and Relevance: according to the results of the study, the relationship of macro- and microeconomic factors in achieving SDG 12 "Responsible consumption and production" by the subjects of "green" entrepreneurship was revealed. The authors propose directions for the implementation of educational measures for the business community in the field of "green" marketing, the influence of ESG factors when changing business models, lean manufacturing, which will help ensure the economic security of subjects of "green" entrepreneurship in the new economic conditions.